The Use of ELENA Towards Students‘ Motivation During the Online Learning in Universitas Negeri Semarang - Putri, Stephanie Priyanto; Fegasanti, Prahda Alifa; Rozi, Fahrur (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
The changes caused by the pandemic of COVID-19 led education sectors in Indonesia to find a new way of teaching-learning processes. Due to the pandemic, students found it difficult to keep themselves motivated to keep up with school materials which could affect their academic from time to time. Furthermore, they still attended the online class but they experienced learning loss because they could not maximize the potential of the e-learning used. This study aimed at evaluating the use of ELENA utilized during the online teaching-learning processes in UNNES which affects students‘ academic motivation. Observations, interview, and 20 Likert-scale items of questionnaire were conducted and distributed to 45 students of English Literature and Education Department of UNNES. The result of this study proved that students had good impressions towards the use of ELENA as a platform to their teaching-learning activities. Some of their answers were the students' quality of work, the students' attitudes towards assignments, the students' confidence, the learning process, the design of ELENA, the students’ behavior in lessons, and the students’ attendance. This research is expected to be one of the references for other researchers to conduct similar studies on this related topic.